“Aqui morremos em pedaços”: morte e mutilação operária na Fortaleza dos Infortúnios (1919-1937) - Costa, Carlos Henrique Brasil (2022)
This research historically studies the mutilation and illness of workers in Fortaleza between 1919 and 1937. This means analyzing the social relations that were conceptualized and helped to legitimize/delegitimize the processes called “accidents at work” in their multiple dimensions and agents. So, analyzing the problem according to the prism of different agents, we investigated how the theme of accidents and occupational illnesses was guided in the first three Brazilian Workers' Congresses and in the legislation of 1919. We developed these topics according to reasearch in the records of congresses from the newspapers A Plebe (1913-1914) and Voz do Trabalhador (1920) and through Decree 3.724/19, respectively.Therefore, the analysis was extended to understand how the press in Ceará positioned itself on the subject, insofar as it was also an agent of legitimation and delegitimization of the recognition of death, mutilation, and illness at work. It was notable that the press in Ceará paid more attention to morbid events directly linked to different facets of railway and industrial activities. We selected newspapers that had addressed, had discussed or had mentioned events related to accidents in the workplace. For this purpose, the periodicals O Combate (1891), Ceará Socialista (1919), O Combate (1921), A Ordem (1916-1933), Imprensa (1924-1932), A Lucta (1914-1924), O Legendário (1933-1934) and A Razão (1937). Finally, we investigated the approaching of debates about labor market control, alcohol control and tensions among port workers in the processes of legitimizing time off work to recover from illnesses and “accidents”. For this purpose, we investigated the Minutes of the ordinary sessions of the Sindicato dos Trabalhadores do Porto de Fortaleza (1927-1933).In these terms, the challenge had launched was to analyze the multiple social relations that involved the problem of the so- called “work accident”, respecting its qualities as a collective political issue, however, without failing to inquire into the singularities of those who live and die for work.